English: English - Miftah Idris; Danang Wahyu Muhammad (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose – The purpose of this study is to analyze the evolution of Alternative Dispute Resolution (ADR) in resolving sharia insurance disputes in Indonesia, as well as to identify global research trends, allocations for scientific investigation, and practical implications. This study not only maps these developments but also provides a structured understanding of the conceptual and procedural evolution of ADR. This contribution offers researchers, policymakers, and practitioners a clearer foundation for improving dispute resolution mechanisms in the sharia insurance sector. Method – The research employs normative legal methodology, incorporating a Systematic Literature Review (SLR) and bibliometric analysis. This approach involved the selection of 16 articles from the Scopus database, utilizing VOSviewer and Bibliometrix software to map scientific advancements and interconnections among research topics. Result – The findings demonstrate a notable rise in publications related to ADR and insurance since 2020, with a primary focus on mediation mechanisms, arbitration, ex gratia, sharia dispute resolution, and the integration of Online Dispute Resolution (ODR). The research identified the necessity for regulatory reform of the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK) and the establishment of a hybrid ADR-ODR model to enhance fairness, efficiency, and legal certainty within the insurance industry Implication – These findings enhance the understanding of how ADR innovations can tackle systemic challenges in sharia insurance dispute resolution and contribute evidence-based recommendations for legal and institutional reform.